Fungicidal properties of green microalgae chlorella vulgaris - Tleukeyeva, Assel Ye; Issayeva, Akmaral; Tleukeyev, Zhanbolat (International Journal of Innovative Research and Scientific Studies, 2025)
Mold fungi are a group of microscopic fungi that have a significant impact on agriculture. They not only worsen the quality of products, but also reduce yields due to damage to plants and seeds. Studying the harm caused by mold is an important task of agronomic science, as it contributes to the development of effective control and prevention methods. The presented article examines the results of the influence of Chlorella vulgaris strains of green microalgae on mold fungi common in vegetable crops. Studies have shown that the use of biofertilizers based on Chlorella vulgaris is environmentally friendly due to their minimal accumulation in the soil. In addition, these fertilizers are economically beneficial, since man-made waste products such as phosphorous slags, sewage sludge, and carbon-containing waste can be used to grow biomass of microorganisms and algae. In the course of research, it was found that fertilizers based on Chlorella vulgaris inhibit the growth of mold fungi Mucor sp. and Aspergillus sp. in the soil and on the surface of seeds of agricultural crops. Compared with traditional fertilizers, their effectiveness reaches 28.6±2.2%. These results confirm the promising use of Chlorella vulgaris to protect crops from mold fungi, improve product quality and increase yields.